Adapting culturally appropriate mental health screening tools for use among conflict-affected and other vulnerable adolescents in Nigeria. (2019) - Kaiser, B. N.; Ticao, C.; Anoje, C.; Minto, J.; Boglosa, J.; Kohrt, B. A.
Abstract : Background: The Boko Haram insurgency has brought turmoil and instability to Nigeria, generating a large number of internally displaced people and adding to the country's 17.5 million orphans and vulnerable children. Recently, steps have been taken to improve the mental healthcare infrastructure in Nigeria, including revamping national policies and initiating training of primary care providers in mental healthcare. In order for these efforts to succeed, they require means for community-based detection and linkage to care. A major gap preventing such efforts is the shortage of culturally appropriate, valid screening tools for identifying emotional and behavioral disorders among adolescents. In particular, studies have not conducted simultaneous validation of screening tools in multiple languages, to support screening and detection efforts in linguistically diverse populations. We aim to culturally adapt screening tools for emotional and behavioral disorders for use among adolescents in Nigeria, in order to facilitate future validation studies. Methods: We used a rigorous mixed-method process to culturally adapt the Depression Self Rating Scale, Child PTSD Symptom Scale, and Disruptive Behavior Disorders Rating Scale. We employed expert translations, focus group discussions ( N = 24), and piloting with cognitive interviewing ( N = 24) to achieve semantic, content, technical, and criterion equivalence of screening tool items. Results: We identified and adapted items that were conceptually difficult for adolescents to understand, conceptually non-equivalent across languages, considered unacceptable to discuss, or stigmatizing. Findings regarding problematic items largely align with existing literature regarding cross-cultural adaptation. Conclusions: Culturally adapting screening tools represents a vital first step toward improving community case detection.